2019
DOI: 10.1111/wrr.12708
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat promotes angiogenesis through HIF‐1α/VEGF/VEGFR2 signaling and accelerates cutaneous wound healing in diabetic rats

Abstract: Diabetic foot ulcers are a major health‐care burden worldwide. One primary cause of the delayed wound healing in diabetic patients is impaired function of the hypoxia‐inducible factor‐1α/vascular endothelial growth factor (HIF‐1α/VEGF) axis, which results in compromised neovascularization in response to hypoxia. In the present study, we aimed to investigate the effect of roxadustat, a novel HIF prolyl‐4‐hydroxylase inhibitor, on angiogenesis and its therapeutic effect on cutaneous wound healing in diabetic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 24 publications
2
71
0
Order By: Relevance
“…Moreover, elevated fatty acids can promote PHD-mediated HIF-1α degradation by decreasing succinate levels in type 2 diabetes. This figure is available as part of a downloadable slideset signalling contributes to impaired wound healing in diabetes, with induction of HIF-1 function promoting wound healing by increasing angiogenesis and fibroblast proliferation and migration in mouse models of diabetes [11,20,21]. As an iron-chelating agent clinically used to treat iron toxicity, deferoxamine (desferrioxamine) can reduce oxidative stress and induce HIF-1 activation, thereby accelerating diabetic wound healing [20].…”
Section: Hypoxia and Hifs In Diabetes And Diabetes Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, elevated fatty acids can promote PHD-mediated HIF-1α degradation by decreasing succinate levels in type 2 diabetes. This figure is available as part of a downloadable slideset signalling contributes to impaired wound healing in diabetes, with induction of HIF-1 function promoting wound healing by increasing angiogenesis and fibroblast proliferation and migration in mouse models of diabetes [11,20,21]. As an iron-chelating agent clinically used to treat iron toxicity, deferoxamine (desferrioxamine) can reduce oxidative stress and induce HIF-1 activation, thereby accelerating diabetic wound healing [20].…”
Section: Hypoxia and Hifs In Diabetes And Diabetes Complicationsmentioning
confidence: 99%
“…Pharmacological induction of HIF-1 promotes wound healing in experimental diabetes models [11,20,21]. Recent preclinical studies in diabetic animal models have shown that PHD inhibition can also prevent the progression of diabetic nephropathy [8,27] and atherosclerosis [29], protect the ischaemic heart [14,51] and peripheral neuron [52], and improve cognitive function [53].…”
Section: Hifs As Therapeutic Targets For Diabetes and Diabetes Complicationsmentioning
confidence: 99%
“…12 Roxadustat (FG-4592) is a novel, potent HIF PHD inhibitor that can stabilize HIF-1a under normoxic or hyperoxic conditions. 17 It stimulates endogenous erythropoietin production and is currently being tested for the treatment of anemia in chronic kidney disease. 18 Roxadustat rescued hepatic Hif1a-gene-knockout neonatal mice from retinal oxygen toxicity, overriding the ablation of hepatic HIF-1a by directly targeting retinal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We also confirmed that the increased vesicles may result from both caveolin‐ and clathrin‐mediated endocytosis pathways. Diabetes elevates the expression of HIF‐1α and vascular endothelial growth factor (VEGF) in the ischemic cerebral microvasculature, 38,50,51 which is accompanied by the disruption of the BBB, increased infarct volume, severe edema formation, and exacerbated neurological deficits. Specific inhibition of endothelial HIF‐1α could partially reverse the damaging effects of diabetes on cerebrovascular injury, suggesting that HIF‐1α activation is one important mechanism underlying increased BBB permeability 38 .…”
Section: Discussionmentioning
confidence: 99%